Application of Linear Body Measurement for Predicting Body Weight of Swamp Buffalo - Galib, I.; Sumantri, C.; Gunawan, A. (Jurnal Ilmu Produksi dan Teknologi Hasil Peternakan, 2017)
The objective of this research was to predict swamp buffalo weight using simple linier body measurement. The height of wither (TB), height of hip (TP), heart girth (LiD), width of chest (LD), dept of chest (DD), width of hip (LP), thurl length (PK), width of rump (LK), body length (PB) were measured in centimeters using measuring rib, one meter ruler, and measuring stick, whereas body weight was determined in kilograms using two tons weighing scale. Linier body measurement ratio between male and female swamp buffaloes was analyzed using t-test analysis. The relationship between linier measurement variables were analyzed using correlation analyisis. Body weight estimator was estimated using best subset regression, linier regression and multiple linier regression analysis. Result of T-test analysis showed that linier body measurement between male and female buffaloes have significant difference in hearth girth, height of hip and body length.  Result of coefficient analysis showed that heart girth and height of hip have a highly correlation with body weight of male and female swamp buffalo. Estimation of swamp buffalo body weight could be estimated through multiple regression with heart girth and height of hip variables. It could be concluded that weight of swamp buffalo can be estimated using multiple linier regression formula, BB = 3.6435LiD + 0.1208TP - 265.43 for male swamp buffalo and BB = 4.1783LiD – 0.3086TP - 305,19 for female swamp buffalo.